ВЫЧИСЛЕНИЕ ПОЛНОГО СЕЙСМИЧЕСКОГО ВОЛНОВОГО ПОЛЯ В ГЕОСРЕДЕ НА ОСНОВЕ НОВОГО МЕТОДА РЕШЕНИЯ ПРЯМЫХ ЗАДАЧ СЕЙСМОАКУСТИКИ - Иванов А.В.; Каплан С.А.; Каракин А.В.; Левченко Т.В.; Левченко В.Д.; Рок В.Е. (My University, 2006)
А new method of full 3D seismic field computation based on a new algorithm of fast numerical solution full system PDE of elasticity is considered in view of application to exploration work.
Keywords: 550.834.01